PENGARUH PRESENTASI BERBASIS POWER POINT TERHADAP MOTIVASI BELAJAR SISWA DI MA NURUL KHOIROH PEKARANGAN KELIR KALIPURO BANYUWANGI - Zaehol Fatah; Ika Ayu Herlina (CV. Denasya Smart Publisher, 2026)
This study aims to determine the effect of PowerPoint-based presentations on students' learning motivation at MA Nurul Khoiroh Pekarangan Kelir Kalipuro Banyuwangi. The background of this research is based on the low learning motivation of students, characterized by a lack of active participation, minimal attention to the subject matter, and low initiative in asking questions or engaging in discussions during the learning process. This study employed a qualitative and quantitative approach, with data collection instruments in the form of learning motivation questionnaires administered to 16 female students as respondents. Data were analyzed using qualitative descriptive analysis and descriptive statistical techniques. The results showed a significant increase in students' learning motivation after the implementation of PowerPoint-based learning, with the average score rising from 58.8 in the pre-test to 78.6 in the post-test. All students experienced a shift in motivation category from moderate to high. Therefore, it can be concluded that the use of PowerPoint-based presentations has a positive and significant effect on students learning motivation at MA Nurul Khoiroh Pekarangan Kelir Kalipuro Banyuwangi.